1997
DOI: 10.1111/j.1553-2712.1997.tb03739.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiphasic Anaphylaxis: An Uncommon Event in the Emergency Department

Abstract: Objective:To determine the rate of clinically significant recurrence of symptoms in patients treated for anaphylaxis in the ED. Methods: Retrospective chart review of out-of-hospital, ED, and hospital records over a 4.5-year period (July 1991 to December 1995) at a university hospital ED with an annual patient volume of 60,000. Subjects were ED anaphylaxis patients with 2 2 of the following 3 organ systems involved: cutaneous, respiratory, and cardiovascular. The major outcome criterion was recurrence of sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 11 publications
0
30
0
1
Order By: Relevance
“…The occurrence of biphasic reactions has been established in the literature and appears to occur in 1% to 20% of anaphylactic reactions (as depicted in Table II). 8,11,27,[29][30][31][32][33][34] In a study evaluating patients with fatal or near-fatal food reactions, approximately 20% of patients experienced a biphasic reaction, indicating that biphasic reactions might be more likely in patients who present initially with severe symptoms. 11 The reported time intervals between the initial reaction Adapted from Smit et al 8 and the onset of the second phase ranged from 1 to 72 hours.…”
Section: Observationmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of biphasic reactions has been established in the literature and appears to occur in 1% to 20% of anaphylactic reactions (as depicted in Table II). 8,11,27,[29][30][31][32][33][34] In a study evaluating patients with fatal or near-fatal food reactions, approximately 20% of patients experienced a biphasic reaction, indicating that biphasic reactions might be more likely in patients who present initially with severe symptoms. 11 The reported time intervals between the initial reaction Adapted from Smit et al 8 and the onset of the second phase ranged from 1 to 72 hours.…”
Section: Observationmentioning
confidence: 99%
“…11 The reported time intervals between the initial reaction Adapted from Smit et al 8 and the onset of the second phase ranged from 1 to 72 hours. 11,27,[30][31][32][33][34] Unfortunately, no reliable clinical predictors have been identified to enable the identification of patients at increased risk of a biphasic reaction, although some studies have suggested that patients requiring higher doses of epinephrine to control initial symptoms or delayed administration of epinephrine might be associated with increased risk of a biphasic reaction. 11,15,33,34 Generally, the same organ systems are involved in the initial and secondary reaction.…”
Section: Observationmentioning
confidence: 99%
“…A delayed onset to the development of symptoms after the initial exposure to the antigen [4,17], and oral ingestion of antigen [4,13] have been noted as potential predisposing factors in two reports thus far, however, many studies that specifically looked for these risk factors were unable to confirm the same [15,16,[18][19][20]. Scranton et al reported biphasic reactions after immunotherapy-induced anaphylaxis [21] further confirming that the route of antigen delivery need not be oral to experience a biphasic response.…”
Section: Predictors Of Biphasic Reactivitymentioning
confidence: 91%
“…They described an overall incidence rate for these reactions of 5.8%. Subsequent retrospective analyses continued to report relatively low incidence rates, such as 2% (from Cianferoni et al's review of 113 inpatients [14]), 3% (from Brady et al's ED review [15]), and 6% (from Lee and Greenes pediatric inpatient series [16]). The most recently published retrospective analyses further suggests relatively low incidence rates of 5.3% and 11% for biphasic responses [17,18].…”
Section: Epidemiology and Incidence Of Biphasic Anaphylaxismentioning
confidence: 99%
See 1 more Smart Citation